Adapting to the New Frontier The Transformative Role of Academics in Shaping Higher Education - Sershan, Naidoo; Mansingh, Ara; Naidoo, Kiveshni; Uddin, Razack Sheriff; Singh, Mishka (Acitya: Journal of Teaching and Education, 2025)
The higher education trajectory has transformed significantly since 2020, largely due to the SARS-CoV-2 pandemic. This period saw both students and academics navigating personal and professional transitions, leading to mental health and work-life balance challenges. Education 5.0, characterized by extensive use of technology, calls for a reassessment of current teaching practices and an exploration of the evolving role of academics in the post-2025 higher education space. Academics are crucial in driving research, designing curricula, and mentoring students. This study is grounded in Gagne’s Conditions of Learning Theory, the Technological Pedagogical Content Knowledge (TPACK) model, and Technological-Motivational-Learning Theory. The focus is on envisioning how the academic landscape should adapt to meet the needs of Generation Alpha, who will enter higher education in 2029. There is a need to nurture intellectual curiosity, inspire critical thinking, and prepare students for future challenges. This study reviewed existing literature to analyze shifts in South African higher education, challenging traditional models and promoting institutional adaptability. Secondary data analysis was employed to envision the evolving role of educators in the post-2025 higher education environment. Findings highlight the current needs of Generation Z and the necessity for academic systems to upskill in preparation for Generation Alpha. Recommendations include embracing activated online pedagogies, upskilling academics, and utilizing EdTech and gamification in higher education. This approach aims to reshape the academic landscape to better cater to the needs of future cohorts, emphasizing the importance of disruptive technology and digital pedagogical knowledge.